BERBAGAI ASPEK TENTANG MALARIA DI KABUPATEN PESAWARAN, PROVINSI LAMPUNG - Ritawati Ritawati; Yanelza Supranelfy (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2018)
Malaria is one of infectious diseases that still affect health problems in Indonesia. Pesawaran District, Lampung is a malaria endemic area, Annual Parasite Insidense (API) for 5 years (2013-2017) including areas with High Case Insidence (HCI) because it has API> 5 ‰. Efforts are made towards malaria-free areas that is integrated malaria control. This requires local entomological data primarily related to species, malaria morbidity, community behavior towards malaria and data on the use of anti-malarial drugs. The method used in the writing of literature study through the study of books, articles, and scientific journals from 2008 to 2017. API Pesawaran District in 2017 highest is 7,5‰ for 10 years (2008-2017 ). Anopheles spp, found in Pesawaran District are Anopheles barbumbrosus, An. nigerrimus, An.nitidus, An peditaeniatus, An.sundaicus, An. barbirostris, An. annularis, An. minimus, An. kochi, An. aconitus, An. tessellatus, An. vagus, An. subpictus, An.indefinitus, An. maculatus and An. hyrcanus group. Community attitudes found that the variables associated with malaria incidence are the habit of going out at night, the installation of wire netting, the density of the walls of the house, the use of mosquito nets at night, the use of anti-mosquito / repellent and the use of body covering. The use of ACT as an anti malarial drug especially Falciparum in Pesawaran District, Lampung is still adequately with highest failure prevalence was 11.59% and the lowest at 2.1%.